Comparative study on density of the cutworm complex (Lepidoptera: Noctuidae) for different environments and predecessor crops in the subhumid region of central pampas (Semiárida, 2018)
The present study was performed with the objective of determining whether the density of cutworms is affected by the type of predecessor crop and field environment. The effect of each particular predecessor crop was assayed on three paddocks selected in 2014 and another three in 2015. The evaluations were done on stubble from the following grain crops: earlysown soybean (ES), latesown soybean (LS), sunflower (S) and maize (M). Sampling was performed at both lowground and highground sites in each paddock for determination of the density of cutworms on five and ten 1 m2 subsamples collected in 2014 and 2015, respectively. Thirty cutworms were bred to adulthood each year for their identification. Such experimental assessment showed that Agrotis robusta was the predominant species. Analysis of variance for density of cutworms was performed following a factorial design considering predecessor crop, paddock environment and year as treatments. The three of these factors affected the density of cutworms and did not show interactions with each other. Observed density values of cutworms were 0.17, 0.4, 1.7 and 2.88 m2 in M, S, LS and ES stubbles, respectively. Cutworm density was higher in 2014 and for lowground sites. These results allow the identification of predecessor crops and field environments holding different risk of damage by cutworms, contributing in that way to the development of more efficient sampling protocols and the integrated management for that kind of plague.DOI: http://dx.doi.org/10.19137/semiarida.2017(02).2935